Association of Arterial Stiffness with Cardiovascular Outcomes in Hypertensive Patients: A Systematic Review and Meta-Analysis - Patel, Rutvij; Baloch, Zara; Hameed, Babar; Pathan, Sadaf; Jamali, Ayesha Ghazal; Indiresh, Dhruv; Rongali, Dinesh Aravind; Ullah, Imdad; Khatri, Suman; Naz, Falak (Cardiology and Cardiovascular Medicine, 2025)
Arterial stiffness is an identified marker of subclinical organ harm and cardiovascular hazard, especially in hypertensive patients. The aim is to compare the association among arterial stiffness and cardiovascular results, inclusive of major adverse cardiovascular events (MACE), cardiovascular (CV) mortality, and all-cause mortality, in hypertensive patients. Seven observational research meetings with predefined eligibility criteria were included. Data were synthesized the usage of a random-consequences version, and heterogeneity was assessed the use of the I² statistic. The meta-analysis demonstrated a significant 29% increased risk of major adverse cardiovascular events (MACE) per unit increase in arterial stiffness (RR 1.29, 95% CI 1.13–1.48; p = 0.0002), with negligible between-study heterogeneity (I² = 0%). In contrast, no statistically significant associations emerged for cardiovascular mortality (RR 1.22, 95% CI 0.92–1.61; p = 0.16) or all-cause mortality (RR 0.93, 95% CI 0.72–1.21; p = 0.61), both outcomes also exhibiting minimal heterogeneity (I² = 0%). Arterial stiffness, as measured with the aid of pulse wave speed (PWV) and AASI, is a huge predictor of MACE in hypertensive patients; however, isn't related to CV or all-cause mortality within the analyzed observation durations.